Notes and News - Tracey, Hugh (International Library of African Music, 1963)
Tina may have been a Nyasa - George Byrd, American musician on Unesco mission to Ethopia - Striking a new note - Miss Luba performed in Washington, D.C. - Conference of African Traditional Music - Kenya's National Anthem -
Keywords: African Music